Prussian *Grubrius ‘god of spring and vegetation’ in perspective of the Italic pantheon - Blažek, Václav; Běťáková, Marta Eva (Baltistica, 2014)
The god originally called *Grubrius (or merely *Grubius), worshipped by Old Prussians in connection with vegetation, seems originally to bear a name of a specific tree species. The etymological analysis suggests a relation to the Slavic dendronym *grabъ & *grabrъ "hornbeam".The Latin and German chronicles recorded his name together with the prefix per / par "for" that was part of the name of the festival dedicated to this god. In the level of theonyms, the closest cognate appears in the Umbrian theonym *Grā̌bovius, serving as an epithet of three Umbrian gods, Vofionos, Mars, and especially Iove (Iuppiter), the thunder-god.
Keywords: Prussian pantheon; Italic pantheon; thunder-god; theonyms; dendronyms; etymology